Self-Harm Behaviour, Psychopathological Distress and Suicidal Ideation in Normal and Deliberate Self Harm Outpatient's Adults - Muhammad Aqeel; Hafiz Haseeb Nisar; Tasnim Rehna; Ammar Ahmed (Journal of the Pakistan Medical Association, 2021)
Objective: The purpose of present research was to examine the association among adverse suicidal ideation, deliberate self-harm, anxiety, stress, and depression in normal as well as deliberate self harm adults in Pakistan. Moreover, to examine the mediating role of deliberate self harm in the relationship between suicidal ideation, depression, anxiety, and stress. Methods: A cross-sectional research has been carried at the Department of Psychiatrist, Military Hospital Rawalpindi, Pakistan from January 2017 to July 2017. Two hundred participants (Normal adult students, n= 100; Patients with deliberate self harm, n=100) were recruited psychiatric outpatient consultations from Military Hospital Rawalpindi in Pakistan. Psychiatric examination comprised of a face to face interview based on Mental Status Examination to incorporate both afore mention samples. Moreover, Psychiatric evaluation was performed by included Self Harm Inventory, Beck Scale for Suicide Ideation, Depression Anxiety and Stress Scale. Results: A comparative analysis between the group of normal and deliberate self harm adults showed statistically significant differences related to: depression, anxiety, and stress. Results reveal that normal adults had higher prevalence of deliberate self harm, anxiety, and depression than adults with deliberate self harm. This study’s findings reveled that deliberate self harm fully mediated among suicidal ideation, depression, stress, and anxiety in adults with deliberate self harm. Conclusion: This study’s results are aligned with attempted suicide and broad depression theory signifying that anxiety, stress, and depression are related and therefore predict significant suicidal ideations among adults with deliberate self harm. Keywords: Suicidal ideation, deliberate self-harm, anxiety, depression, stress, Continuous...